Association between ectopic pancreatic and hepatic fat and metabolic risk factors in children with non‐alcoholic fatty liver disease. Issue 10 (4th May 2021) - Lee, Eun Hye; Kim, Ji Young; Yang, Hye Ran
Summary: Background: Few studies have reported an association between ectopic pancreatic and hepatic fat and metabolic factors in children with non‐alcoholic fatty liver disease (NAFLD). Objectives: We investigated this association and also the factors associated with pancreatic and hepatic fat deposition in children with NAFLD. Methods: This cross‐sectional study investigated 65 children with NAFLD (49 boys, 13.0 ± 3.2 years, mean body mass index z‐score 2.5 ± 1.2), who underwent liver biopsy and magnetic resonance imaging–based proton density fat fraction, as well as anthropometry, laboratory tests, body composition analysis, and hepatic fat fraction (HFF) and pancreatic fat fraction (PFF) measurements. Results: HFF and PFF were 4.2%–49.9% (median 24.3) and 0.4%–26.9% (median 3.8), respectively. HFF was not significantly correlated with PFF. HFF was correlated with total body fat% ( r  = 0.329, p  = 0.010) and γ‐glutamyl transpeptidase (GGT) ( r  = 0.260, p  = 0.040), while PFF was correlated with the diastolic blood pressure ( r  = 0.253, p  = 0.045), GGT ( r  = 0.335, p  = 0.007) and fasting plasma glucose ( r  = 0.417, p  = 0.001). Multiple linear regression analysis showed that HFF was significantly associated with sex, age, body fat% and GGT, whereas PFF was associated with hypertension and fasting plasma glucose levels but not insulin resistance. Conclusions: HFF was associated with sex, age and body fat in children with NAFLD, while PFF was associated with hypertension and increased fasting plasma glucose, which suggests that the pathophysiology of ectopic fat accumulation varies across organs in children with NAFLD. Abstract :